Jim Crow North and Fair Housing Enforcement - Charles S. Bullock, III; Charles M. Lamb (Columbia Journal of Race and Law)
This article investigates how federal, state, and local government agencies enforce the federal Fair Housing Act of 1968 (also known as Title VIII of the Civil Rights Act of 1968) in Northeastern states, which are referred to here as the Jim Crow North. Focusing on data obtained from the U.S. Department of Housing and Urban Development (HUD) under the Freedom of Information Act (FOIA), this study measures the extent to which the thirteen Northeastern states—from Maine to Virginia—decided Fair Housing Act complaints in favor of Black and Latinx Americans from 1989 to 2010.